GENERATION AND PHYSICOCHEMICAL CHARACTERIZATION OF CHICKEN EGG YOLK ANTIBODIES (IgY) AGAINST Salmonella typhimurium - T. DIRAVIYAM; M. MENAKA; R. MAHENTHIRAN; A. MICHAEL (International Journal of Pharma and Bio Sciences, 2013)
Salmonellosis is one of the most important bacterial diseases with economic concern to all phases of the poultry. The study was aimed to generate chicken IgY against Salmonella typhimurium and its physicochemical characterization to unbolt the obstacles for the usage of IgY as therapeutic agent in Poultry. Salmonella typhimurium whole cell antigen was prepared and immunized in white leghorn chickens. The immune eggs were collected and IgY was purified from the yolk by PEG extraction method, the purity of the IgY extract was estimated by SDS-PAGE. The peak titer of Anti-S.tyhpimurium-IgY in egg yolk was observed after 35th day from the first immunization by ELISA. Total IgY concentration was found to be 30.24 ± 0.25 mg/ml after 25th week of bird’s age. The specific reactivity of IgY was relatively stable at 60oC and then significantly decreased at 70oC. The pH stability of IgY was observed between pH4.0 and pH 10. IgY was more resistant to Trypsin compared to pepsin.